Discovery of Aphis ruborum (Hemiptera: Aphididae) and Aphelinus varipes (Hymenoptera: Aphelinidae) on Cultivated Strawberry in Mississippi, USA. Issue 3 (8th June 2019) - Riddick, Eric W; Miller, Gary L; Owen, Christopher L; Bauchan, Gary R; Schmidt, Jason M; Gariepy, Tara; Brown, Richard L; Grodowitz, Michael J
Abstract: An adventive aphid and novel host–parasitoid association from cultivated strawberry ( Fragaria × ananessa Duch. cv. Chandler; Fragaria × ananessa Duch. cv. Camarosa) in Mississippi, USA are reported herein. The aphid, first detected in high tunnel cultivation, was found predominately on newly emerged, not fully developed leaflets of daughter plants in the Fall of 2016. By 2017, aphids and their associated mummies were observed on fully developed leaflets on mother plants of both cultivars. The aphid was identified as Aphis ruborum (Börner & Schilder) using morphology and DNA barcoding studies. In addition, DNA barcoding identified parasitoid adults emerging from aphid mummies as two cryptic species, Aphelinus varipes (Foerster) and Aphelinus albipodus Hayat and Fatima. Occurrence of A . ruborum in Mississippi represents a new state record and the eastern-most established record in the United States. The A . ruborum – A . varipes or A . albipodus host–parasitoid association is reported for the first time anywhere in the world.